Exploring species and pests of stingless bee in Bengkaung Village and Buwun Sejati Village, West Lombok - Jihadi, Amrul; Supeno, Bambang; Sarjan, Muhammad; Haryanto, Hery (Jurnal Agrotek Ummat, 2024)
Stingless bees are highly diverse insects in Indonesia and play a role in providing ecosystem services by helping to pollinate crops and produce honey. However, pests present as an obstacle that can disrupt and reduce the number of individual bees and can even cause bees to escape from their nests. The aims of this research are to identify the species of stingless bees bred by beekeepers and to identify pests that affect stingless bees in colony boxes. The research was conducted in Bengkaung and Buwun Sejati villages from July to September 2023. The method used in this study was direct observation and survey of stingless beekeepers. Stingless bee and pest samples from boxes containing various species of stingless bees were taken to the Plant Protection Laboratory at University of Mataram for identification. Results show that four species of stingless bees are cultivated, namely Tetragonula fuscobalteata, Tetragonula biori, Tetragonula clypearis and Tetragonula sapiens. The pest species found were lizards (Gekkonidae), ants (Formicidae), spiders (Archidae), wasps (Vespidae), mites (Varroidae), beetles (Histeridae) and Assasin Bug (Reduviidae).